Perlindungan Konsumen, Terhadap Produk Peralatan Makan yang Mengandung Melamin Palsu (Lex Jurnalica, 2011)
Tableware used in the past only made of glass / glass, kramik, plastic. With the development in various fields of science, it is currently known tableware made of melamine. Melamine is known for excellence that is not easily broken and light. Melamine is more demand led to increased production of melamine by the domestic manufacturers and overseas production of melamine. This research will discuss about the rights and obligations of consumers and businesses against products containing melamine tableware? How the security products that contain melamine tableware fake? And How is legal protection for consumers against products containing melamine tableware fake? The purpose of this study was to clarify the rights and obligations relating to consumer products containing melamine tableware false, then to explain the effects of products containing melamine tableware false, and to explain the legal protection for consumers against products containing melamine tableware false. The methodology used in this study is the Normative research is by looking at the rules relating to consumer protection as well as the issues being raisedKeywords: Protecting, Consument, Melamin